Studies of Wound Healing Activity and Irritation Test of Chili (Capsicum frutescens L.) Leaves Gel on Rats (Rattus novergicus): (Studi Aktivitas Penyembuhan Luka Dan Uji Iritasi Gel Daun Cabai Rawit (Capsicum frutescens L.) Pada Tikus (Rattus novergicus) - Lebang, Julianri Sari; Siampa, Jainer Pasca; Nurmiati, Nurmiati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Chili pepper (Capsicum frutescens L.) leaves have been used empirically as wound healing caused by sharp objects. Several studies showed that it has antibacterial and wound healing activities. This study aims to formulate gel from chili leaves extract, then determine wound healing activity and irritating properties on rat’s skin. Gel was formulated by using various types and concentrations of gelling agents, consisted of Carbopol 0.5%, 0.75%, 1% and hydroxy propyl methyl cellulose at 2.5%, 5% and 7.5% respectively. Cycling test was conducted to determine the physical stabilities. The results showed that all formula has no altered on organoleptic properties and pH value. Gel of 0.5% Carbopol (F2) and 7.5% of HMPC (F5) has no change in spreadability and adhesion properties. Based on statistical analysis using paired t-test and one-way ANOVA, it concludes that F2 and F5 were physically stable and further evaluated as wound healer. Wound healer evaluation showed that the healing time (days) of Carbopol based gel (F2) was 10.2±1.26 and HPMC based gel was 8±0.82. The length of incision wound (cm) at 8th day was 0.5±0.183 for F2 and 0.06±0.071 for F5. Statistical analysis of healing time showed p<0.01 and wound length showed p<0.05 indicated that F5 (contained 5% HPMC) was significantly different compared to negative control. The results of the irritation test showed that gel formulas were not causing erythema and edema on rat’s skin. It can be concluded that gel of chili leaves extract that formulated with 5% of HPMC has wound healing activity and safety to be used.